Cycling performance and efficiency using a new chainring - Belen, L.; Micallef, J. P.; Habrand, M.; Le Bris, S.; Le Gallais, D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Cycling performance depends on physiological (Lucia et al. 1998), and biomechanical variables (Gonzalez et al. 1989). On the other hand, cycling performance depends on material and bicycle design, and researches recently focused on prototype chainrings. Elliptical and eccentric chainrings failed to improve cycling performance (Henderson et al. 1977; Cullen et al. 1992). In contrast, chainrings using change in crank arm length as a function of crank angle (i.e. eccentric chainrings) allowed to improve cycling performance (Hue et al. 2001) and efficiency (Zamparo et al. 2002). The aim of the present study was to investigate a new prototype chainring (PC) which showed two particularities: out of line of pedal cranks (figure 1), and change in crank arm length during the pedaling cycle (figure 2). Moreover, PC was designed to induce higher mean net torque (TN mean) than standard chainring (SC) during the pedaling cycle. Methods Eleven subjects performed an incremental exercise test, and seven subjects performed an "all-out" 1-km test, using PC and SC, respectively. During incremental cycling, cardioventilatory variables (Heart rate, oxygen uptake [VO2], carbon dioxide production, respiratory ratio, respiratory equivalent for O2 and CO2, breathing frequency and tidal volume) were recorded every min using an automated respiratory system. During 1-km test, mechanical and time variables (mean speed, maximal speed, mean torque, maximal torque, minimal torque, time to reach maximal speed, time to achieve 1-km) were measured continuously from an instrumented chain adjuster. In addition a fatigue percentage was calculated, corresponding to maximal speed minus speed at 1-km achieved, and divided by maximal speed (adapted from Bar-Or 1987). Discussion/Conclusion PC in the present study failed to improve cycling performance and efficiency during incremental exercise. This result may be related to additional parts of prototype which increased weight and frictions, compared with standard chainring. Theoretical advantage of PC would thus be counterbalanced by unexpected muscular work leading to similar VO2. On the other hand, 1-km test did not investigate cycling efficiency, but the possibility to cycle as fast as possible. PC failed to improve cycling performance during this test. However, the time need to reach maximal speed, and the fatigue percentage were significantly lower with PC compared with SC. This result suggested that prototype chainring exhibited potentialities to improve performance in brief and explosive cycling situations where sprint and maximal speed are required.